2020
DOI: 10.33448/rsd-v9i11.10103
|View full text |Cite
|
Sign up to set email alerts
|

The convenience of non-conventional methods for evaluation of the culinary quality of beans

Abstract: The standard Mattson method to evaluate the cooking time of beans on breeding programs presents disadvantages. We have tested and improved a non-conventional method previously proposed to evaluate the percentage of cooked grains on an automatic pressure cooker. It showed a similar trend as Mattson’s for the cooking behavior of contrasting genotypes, but the first showed a higher correlation with sensory tests. Differently, it is closer to the Brazilian domestic bean preparation. It is a simple and more afforda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Freshly harvested grains have less resistance to cooking. However, when stored under ambient conditions, carioca beans increase their resistance to cooking or take longer to cook (Alvares et al, 2020;Bento et al, 2020aBento et al, , 2020bde Farias et al, 2020;Alvares et al, 2020;Bento et al, 2021a). Navarro, 2019).…”
Section: Resistance To Cooking/cooking Timementioning
confidence: 99%
See 3 more Smart Citations
“…Freshly harvested grains have less resistance to cooking. However, when stored under ambient conditions, carioca beans increase their resistance to cooking or take longer to cook (Alvares et al, 2020;Bento et al, 2020aBento et al, , 2020bde Farias et al, 2020;Alvares et al, 2020;Bento et al, 2021a). Navarro, 2019).…”
Section: Resistance To Cooking/cooking Timementioning
confidence: 99%
“…These changes occur in the integument of some carioca bean cultivars because some genotypes darken very quickly, and the bean also hardens itself rapidly. These processes reduce the culinary quality of the carioca beans economically, depreciating the product (Bento et al, 2020a(Bento et al, , 2020bde Farias et al, 2020;Bento et al, 2021a).…”
Section: Resistance To Cooking/cooking Timementioning
confidence: 99%
See 2 more Smart Citations
“…Based on FAO data, the amount of bean split produced in the world is around 3.02 million tons (FAO, 2019; Gomes et al., 2015). Another factor that results in economic loss is the browning of the seed coat (mainly in Pinto bean cultivars), which is associated by consumers with the hard‐to‐cook (HTC) problem (Bento, Bassinello, et al., 2020; Bento, Lanna, et al., 2020; Bento, Ribeiro, et al., 2021). However, it has been confirmed that both broken, and HTC grains have similar nutritional characteristics and technological applicability to freshly harvested whole grains (Alves et al., 2016; Alves et al., 2016; Berrios et al., 1998, 1999; de Lima et al., 2019).…”
Section: Introductionmentioning
confidence: 99%